(untitled) (Journal of Hama University, 2022)
The current research aims to know the impact of applying knowledge management processes on quality assurance of higher education institutions in education colleges of universities (Damascus - Al-Baath - Hama) and to identify the differences in the average responses of the sample members about both the application of knowledge management processes and the quality assurance of higher education according to the (gender, university, and the academic rank) variables The research sample consisted of (133) faculty members chosen randomly from the three universities, and the research tool consisted of a questionnaire consisting of 56 items distributed over two axes: the knowledge management Applications axis and it consists of 32 items distributed in three dimensions, and quality assurance of higher education axis consisting of 24 items divided into five dimensions The results of the research showed the existence of an impact of applying knowledge management processes in ensuring the quality of higher education institutions in the selected universities. It also showed that there are statistically significant differences between the averages of the responses of the sample members in the focus of knowledge management processes according to the university variable and the academic rank, and the existence of differences between the answers in the axis of ensuring the quality of Higher education according to the university variable only, and the absence of statistically significant differences in the axes of knowledge management processes and ensuring the quality of higher education according to the gender variable The research presented a number of proposals, the most important of which is the adoption of knowledge management as an entry point to develop and improve the individual and institutional performance of higher education institutions, and designing a program Quality assurance in universities, taking into account the components of the quality assurance program in higher education, by making use of and seeing best practices in this field, and working on the integration and interaction of both knowledge management and quality approaches in achieving the goals and objectives of universities.